2002
DOI: 10.1021/pr025511u
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Properties of Yersinia pestis Caf1 Capsular Antigen and Their Possible Role in Fulminant Development of Primary Pneumonic Plague

Abstract: Yersinia pestis capsular antigen Caf1 is shown to be a beta-structural protein that in polymeric form possesses very high conformational stability. Different approaches show that a dimer is the minimal cooperative block of Caf1 adhesin. Caf1 dimer interacts effectively with IL-1 receptors of human macrophage and epithelial cells. The specificity of such interaction is confirmed by the inhibition of IL-1alpha binding by Caf1. The Caf1 role in pneumonic plague pathogenesis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
0
6
0
2
Order By: Relevance
“…More recently, evidence of possible immunomodulatory effects of caf gene products has been reported. Interactions between Caf1 dimers bound to the Caf1M chaperone and interleukin 1 (IL-1) receptors on epithelial cells and macrophages, and between the Caf1A outer-membrane usher protein and IL-1␤, have been demonstrated (1,2,73). Proinflammatory cytokine induction due to macrophage activation by Caf1 has also been reported (57,58,60).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…More recently, evidence of possible immunomodulatory effects of caf gene products has been reported. Interactions between Caf1 dimers bound to the Caf1M chaperone and interleukin 1 (IL-1) receptors on epithelial cells and macrophages, and between the Caf1A outer-membrane usher protein and IL-1␤, have been demonstrated (1,2,73). Proinflammatory cytokine induction due to macrophage activation by Caf1 has also been reported (57,58,60).…”
Section: Discussionmentioning
confidence: 97%
“…Small amounts of F1 subunits and the Caf1A outer membrane usher protein showed affinity to the IL-1 receptor on macrophages and epithelial cells and to IL-1␤, respectively. This adhesin or anti-immunity potential has been suggested to be important early in infection (1,2,73). In addition, Y. pestis has evolved to be transmitted along with flea saliva into the dermis, which is not well mimicked by subcutaneous or i.d.…”
Section: Discussionmentioning
confidence: 99%
“…Высказано предположение о том, что димеры Caf1, способные взаимодействовать с рецепто-рами интерлейкина-1 ряда иммунокомпетент-ных клеток, могут обеспечивать тесный кон-такт между Y. pestis и эукариотической клеткой мишенью за счет их крепления на Caf1A ашере, расположенном во внешней мембране бактери-альной клетки [41]. Подобный тесный контакт необходим для инициации системы секреции 3-го типа, обеспечивающей доставку цитоток-сических эффекторных Yop белков в клетку ми-щень хозяина.…”
Section: роль капсульного антигена в патогенезеunclassified
“…Было принято считать, что в клет-ках, выращенных при температуре 28°С, капсула не образуется, а фракция I может быть выявле-на после дезинтеграции клеток [58]. Однако ис-пользование высокочувствительных методов по-зволило обнаружить у клеток чумного микроба, выращенных при температуре 28°С, капсульный антиген, расположенный на поверхности клетки [41]. Продукция F1 возможна в широком диапа-зоне pH с максимальным выходом капсульного антигена в интервале pH от 6,3 до 7,3 [76].…”
unclassified
“…The previous findings by Weening and coworkers showed that differences in virulence with caf1 was predicated on the mouse background [62]. Although there appears to be evidence that the capsule plays a minor role in virulence, depending upon host; it has been shown that minute amounts of the F1 subunits and the outer membrane Caf1A protein have an affinity to the IL-1 receptor on macrophages and to IL-1β expression by epithelial cells [63][64][65]. This may play a role in early infection by conferring adhesion or anti-immunity potential [54].…”
Section: The Capsular Antigen Fraction 1 (Caf1) Capsulementioning
confidence: 98%